Mycosis fungoides with a dramatic course in a patient with a history of pyoderma gangrenosum – a case report - Nowowiejska, Julia; Świstak, Magdalena; Baran, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Mycosis fungoides is the most common primary cutaneous lymphoma characterized by a chronic progressive course. Advanced stages may be associated with extracutaneous manifestations and prognosis may be poor. Objective . To describe a rare case of mycosis fungoides characterized by a dramatically rapid course. Case report . A 64-year-old male patient with a history of pyoderma gangrenosum was hospitalized three times. The first symptom was ulceration of the cheek which was surgically removed. Soon afterwards, multiple erythematous-scaly and infiltrative lesions appeared, as well as tumours prone to ruptures and ulcerations. Computed tomography imaging of the chest and abdomen revealed enlarged lymph nodes. It was only after the third histopathological examination that lymphoma was diagnosed. Methotrexate and PUVA were introduced, however despite therapy the disease progressed rapidly and the patient’s condition worsened significantly. Eventually, the man died at home a week after the last hospitalization. Conclusions . Mycosis fungoides is usually characterized by low malignant potential and long-term survival. However, a more dramatic course is also possible. Primary lesions are typically non-specific, and histopathological examination is crucial for the diagnosis.